THE EFFECT OF INCREASING VALUE ADDED TAX (VAT) AND INCOME ON CONSUMER PURCHASING POWER IN SMARTPHONE PURCHASE (CASE STUDY: ITC ROXY MAS) - Muhammad Fakhri; Saparuddin Mukhtar (Yayasan Education and Social Center, 2023)
This study aims to determine the relationship of value added tax and income to people's purchasing power, either simultaneously or partially. The method used in this study is the method of determining the probability sample which uses the area sampling method. Data analysis used in this research is descriptive statistics, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. For analysis method, SPSS Version 25 is used. The results of the hypothesis test concluded: there is a relationship between value added tax and income on consumer purchasing power. In this study, The contribution of Xâ‚ and Xâ‚‚ to Y is 84.2%, meaning that 84.2% of the variable value added tax and income contributes to consumer purchasing power, while the remaining 15 .8% is influenced by other variables